Representatives Illocutionary Acts by the Main Character Found in Fast X Movie - Ni Made Jelianti; I Made Yogi Marantika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study aimed to analyzing illocutionary acts found in Fast X movie. This study entitled "Representative speech Acts found in the main character in Fast X Movie" discusses speech analysis based on the concept of speech acts of the main character. Each utterance shows three types of speech acts namely locutionary, illocutionary and perlocutionary. However, this study only focuses on the discussion of illocutionary speech acts because the meaning and specific purpose of a person's utterance are described in detail, so that the meaning of an utterance can be understood better in certain social interactions. The main theory used in analysing illocutionary speech acts in this study is the theory of Yule (1996) and supported by the theory of Leech (1983). Fast X movie was chosen as the data source in this study because of the many illocutionary speech acts spoken by the main actors of the movie. The steps of data collection include observing the movie, making notes on illocutionary speech acts, and grouping the data into several subcategories. This analysis shows that Dom significantly utilizes assertionswith 64 found. This is various communicative functions as an emphasis on his strategic plan, as well as to build and instill confidence in other characters.